Love bites? Pre-copulatory behaviours of whale sharks (Rhincodon typus) at Ningaloo Reef, Western Australia - Barry, Christine; Lester, Emily; Doane, Micheal P.; Ferreira, Luciana C.; Thums, Michele; Gleiss, Adrian C.; Meekan, Mark G. (Frontiers in Marine Science, 2025)
Very little is known about the reproductive behaviours of whale sharks (Rhincodon typus). Here, we describe field observations of courtship behaviour by a whale shark at Ningaloo Reef, Western Australia. We witnessed and recorded following and biting behaviours by a sexually mature male of a smaller female. Following and biting are common events during courtship and copulation of other species of elasmobranchs. Our observations are consistent with earlier reports of courting behaviours in whale sharks provided by fishers, the pilot of a light plane and observations of courtship by a sexually mature male towards females held in aquaria.